Royal Palm Bug, Xylastodoris luteolus Barber (Insecta: Hemiptera: Thaumastocoridae) - Thomas J. Weissling; Forrest W. Howard; Alan W. Meerow (EDIS)
The royal palm bug, Xylastodoris luteolus Barber, is one of the few arthropods that feed on Cuban royal palms, Roystonea regia, which are native to Florida and Cuba. This insect species is the only representative of the small, tropical family Thaumastocoridae in North America.  This document is EENY-097, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 1999. Reviewed: May 2005.